Association between preconception paternal health and pregnancy loss in the USA: an analysis of US claims data. Issue 3 (18th December 2020) - Kasman, Alex M; Zhang, Chiyuan A; Li, Shufeng; Lu, Ying; Lathi, Ruth B; Stevenson, David K; Shaw, Gary M; Eisenberg, Michael L
Abstract: STUDY QUESTION: Is preconception paternal health associated with pregnancy loss? SUMMARY ANSWER: Poor preconception paternal health is associated with a higher risk of pregnancy loss as confirmed in sensitivity analyses accounting for maternal age and health. WHAT IS KNOWN ALREADY: Preconception paternal health can negatively impact perinatal outcomes. STUDY DESIGN, SIZE, DURATION: Retrospective cohort study of US insurance claims database from 2009 to 2016 covering 958 804 pregnancies. PARTICIPANTS/MATERIALS, SETTING, METHODS: US insurance claims database including women, men and pregnancies within the USA between 2007 and 2016. Paternal preconception health status (e.g. metabolic syndrome diagnoses (MetS), Charlson comorbidity index (CCI) and individual chronic disease diagnoses) was examined in relation to pregnancy loss (e.g. ectopic pregnancy, miscarriage and stillbirth). MAIN RESULTS AND THE ROLE OF CHANCE: In all, 958 804 pregnancies were analyzed. The average paternal age was 35.3 years (SD 5.3) and maternal age was 33.1 years (SD 4.4). Twenty-two percent of all pregnancies ended in a loss. After adjusting for maternal factors, the risk of pregnancy loss increased with increasing paternal comorbidity. For example, compared to men with no components of MetS, the risk of pregnancy loss increased for men with one (relative risk (RR) 1.10, 95% CI 1.09–1.12), two (RR 1.15, 95% CI 1.13–1.17) or three or more (RR 1.19, 95% CI 1.14–1.24) components. Specifically, less healthy men had a higher risk of siring a pregnancy ending in spontaneous abortion, stillbirth and ectopic pregnancies. Similar patterns remained with other measures of paternal health (e.g. CCI, chronic diseases, etc.). When stratifying by maternal age as well as maternal health, a similar pattern of increasing pregnancy loss risk for men with 1, 2 or 3+ MetS was observed. A statistically significant but weak association between timing of pregnancy loss and paternal health was found. LIMITATIONS, REASONS FOR CAUTION: Retrospective study design covering only employer insured individuals may limit generalizability WIDER IMPLICATIONS OF THE FINDINGS: Optimization of a father's health may improve pregnancy outcomes. STUDY FUNDING/COMPETING INTERESTS: National Institutes of Health National Center for Advancing Translational Science Clinical and Translational Science Award (UL1 TR001085). M.L.E. is an advisor for Sandstone Diagnostics, Dadi, Hannah and Underdog. No other competing interests were declared. TRIAL REGISTRATION NUMBER: N/A